Energy bricolage in Northern Uganda: Rethinking energy geographies in Sub-Saharan Africa. (September 2019) - Munro, Paul G.; Bartlett, Anne
Abstract: In this paper, we propose the idea of 'energy bricolage' as a way of rethinking how people in Sub-Saharan Africa realise their energy needs on a daily basis. In doing so, we directly challenge dominant framings of energy poverty in Africa by the United Nations and other development agencies that have tended to present the issue as a question of access to the electricity grid; that energy poverty emerges from a lack of access to large-scale infrastructure. Drawing on research from Northern Uganda, we show how households and individuals in Africa can be understood as bricoleurs, making creative and resourceful use of whatever materials at are at hand to try and realise their energy needs and desires. That they engaged in complex geographies of energy: using batteries for torches, photovoltaic power for phone charging and stereos, firewood for cooking, charcoal for selling and petrol for transport. In this sense, beyond the modernist conceptions of energy development as grid electricity access, they are able to craft post-modern energy landscape, one that is neither 'traditional' nor 'modern, ' rather the fragmented product of different social and economic processes. We argue that this conception of energy bricolage allows us to bring a more nuanced perspective for understanding the geographies of energy poverty in Sub-Saharan Africa and other parts of the developing world. We reframe the view of the energy poor as subsistence population eking out pre-modern lives, to one that has complex entanglements with different and changing energy technologies and institutional arrangements.